2000
DOI: 10.2337/diacare.23.1.84
|View full text |Cite
|
Sign up to set email alerts
|

Total homocysteine in patients with type 1 diabetes.

Abstract: OBJECTIVE: Our aim was to study the presence of moderate hyperhomocysteinemia, a risk factor for premature cardiovascular disease, its modifying vitamin factors (folates, vitamins B12 and B6), and lipid risk factors in juvenile type 1 diabetes. RESEARCH DESIGN AND METHODS: A total of 91 patients with type 1 diabetes (46 girls and 45 boys) were studied, with ages ranging from 11 to 18 years, a duration of diabetes from 1 to 15 years, and in pubertal development (stages III, IV, V). In all patients, cholesterol,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
25
2
5

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 2 publications
4
25
2
5
Order By: Relevance
“…In conclusion our results confirm recent data, which report normal level of plasma Hcy in T1DM patients (23). In any case, considering that a trend to higher values of plasma tHcy with the age (r 2 = 0.17, p < 0.001) is more significant in young T1DM than in our control group of the same age, we suggest in such a metabolic situation, the measure of plasma tHcy levels in order to prevent the endothelial damage.…”
Section: Discussionsupporting
confidence: 81%
“…In conclusion our results confirm recent data, which report normal level of plasma Hcy in T1DM patients (23). In any case, considering that a trend to higher values of plasma tHcy with the age (r 2 = 0.17, p < 0.001) is more significant in young T1DM than in our control group of the same age, we suggest in such a metabolic situation, the measure of plasma tHcy levels in order to prevent the endothelial damage.…”
Section: Discussionsupporting
confidence: 81%
“…This study found that HbA 1c is inversely predictive of tHcy levels, although previous investigations have reached conflicting results with regard to glycemic markers in patients with diabetes. Some investigations have found that these markers are positively correlated with tHcy levels (35,36), others have found a negative correlation (37), and still others have found no significant relationship (15,38). The cause of the inverse relationship found here is not obvious.…”
Section: Discussioncontrasting
confidence: 41%
“…With regard to the role of vitamins in the metabolism of methionine, significant inverse relations between at least one of the vitamins involved (folate, B 12 and B 6 ) and plasma tHcy have often been found (Andersson et al, 1992;Ubbink et al, 1998;Pavia et al, 2000;Lim & Heo, 2002;Houcher et al, 2003;Huang et al, 2003;Samman et al, 2003). Laboratory indices of folate (serum folate and RBC-folate), vitamin B 12 and vitamin B 6 showed an adequate supply with these vitamins.…”
Section: Discussionmentioning
confidence: 99%